Applicability of the nutrition and food component of the chair of public health in a public educational institution in Pamplona - Botía-Rodríguez, Irene; Carvajal-Suárez, Lennys; Molina-Rúas, María Paola (Universidad y Salud, 2018)
Introduction: The chair of public health has been implemented in a sustainable and integral way to generate healthy lifestyles and contribute to improving the quality of life. Objective: To evaluate the applicability of the nutrition and food component of the chair of public health in a public educational institution in Pamplona. Materials and methods: A descriptive study was conducted in 108 students from 7 to 11 grades, who answered a survey with Likert-type questions. Results: 40% of the students said they always try to have a balanced and healthy diet in order to avoid eating disorders. 63% considered that the knowledge acquired on breastfeeding has never been applied in the environment in which they develop. In spite of this, women more frequently apply the knowledge acquired with respect to men (P = 0.031). Seventh graders try to have a balanced and healthy diet to avoid eating disorders with respect to other school grades (P = 0.029). Conclusions: Flaws are identified in the applicability of knowledge in nutrition and food, so it is necessary to implement effective educational strategies to encourage the adoption of healthy practices in adolescents.